Transmedia Intertextual Systems as a pedagogical strategy: From The Walking Dead® to The Odyssey - Montoya Bermúdez, Diego (2015)
This paper approach the study of transmedia phenomenon as a set of relationships that involves not only intertextual narrative conditions, but also anthropological. With two goals: first, to structure a system that serves intertextual analysis tool to own transmedia products of the culture industry and the second, to generate possible keys to be used as a pedagogical strategy in the classroom to encourage reading and writing in conjunction with other symbolic systems. So, the article introduces the reader to the phenomenon of transmediality, which is then reviewed proposals from Henry Jenkins and Marsha Kinder that serve as material for developing a transmedia Intertextual System, which applied as a methodology for the analysis of a case of the entertainment industry, The Walking Dead ®. From the above and way of results, the text identifies key for this type of transmedia systems, which are applied as instructional strategies for teaching in basic education levels in secondary and high schools, as evidenced in the The Odyssey study. Finally, in conclusion exposes the importance of exploring the possibilities offered by the study and reflection transmedial in areas that transcend the world of entertainment.